Caregivers' level of knowledge and home- based practices for prevention of Sickle cell disease related complications among children attending Mnazi mmoja hospital in Zanzibar. (2021) - Ali Amour, Mwanahawa; Jumanne, Shakilu
Abstract: Background: Optimal control of Sickle cell disease (SCD) related complications in children is enhanced when caregivers have good knowledge of factors leading to complications and effective home-based preventative interventions. Most SCD care programs incorporate caregivers' education sessions but little is known on the knowledge level and adherence to recommended home based preventative interventions among caregivers of children with SCD. Objective: To evaluate knowledge level and home-based care practices of caregivers of children with SCD attended at Mnazi mmoja Hospital in Zanzibar in relation to occurrence of disease complications. Methods: This was a cross-sectional study of caregivers of children with SCD bringing their children to Mnazi mmoja Hospital in Zanzibar. Caregivers with children aged 6 months to 12 years were enrolled. SCD knowledge and home-based care practices were evaluated using pre-tested scales consisting of 27 and 22 items respectively. Descriptive statistics, bivariate correlation and logistic regression analysis were done using SPSS version 21. Results: A total of 300 caregivers of children with SCD were enrolled, among the caregivers, 53.3% had inadequate SCD knowledge and 52% reported inappropriate home based care practices. Caregivers knowledge level (AOR 2.282, 95% CI [1.021, 5.103] p = 0.044) and home-based care practices (AOR 3.030, 95% CI [1.338, 6.862] p = 0.008) were significantly associated with occurrence of disease complications. Conclusion: Inadequate caregivers' level of knowledge and poor adherence to home-based care practices are significantly associated with occurrence of SCD related complications. We recommend review of the modality and contents of health education given to caregivers to identify gaps to be improved for better Sickle cell disease control.